Kualitas dan tingkat kesukaan konsumen terhadap virgin coconut oil (VCO) hasil dari metode penggaraman - Satmalawati, Endah Mulat; Naisali, Hyldegardis; Tahun, Susana Kristina; Nahak, Delfrida Karlani (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Coconut oil processing using traditional methods involving high temperatures can damage the oil's structure and quality, leading to rancidity and reduced nutritional value. To address this, alternative methods like salting are essential for producing high-quality Virgin Coconut Oil (VCO) that meets industry standards. This study aims to evaluate the effect of salt concentration and incubation time on the yield, water content, free fatty acids, and organoleptic properties of VCO. The research employed a Completely Randomized Design (CRD) with two factors: salt concentration (4 grams, 6 grams, and 8 grams) and incubation time (12, 24, and 36 hours). Statistical analysis using ANOVA at a 95 % significance level followed by post-hoc tests was conducted to assess the treatment differences. Results showed that a 6-gram salt concentration combined with a 12-hour incubation yielded the best results in terms of yield, water content, and overall quality. The water content ranged from 0.06 % to 0.14 %, adhering to the Indonesian National Standard (SNI 7381:2008), which limits water content to 0.2 %. Free fatty acids were also low, with an acid value ≤ 0.2 %, well within SNI limits. Organoleptic tests revealed that consumers preferred VCO made with 6 grams of salt and a 12-hour incubation. This formulation produced oil with a clear, attractive color, a fragrant aroma, and a pleasant coconut flavor. Overall, the salting method proved highly effective for producing premium VCO. Not only did the oil meet standard quality parameters, but it also had a longer shelf life, making it suitable for health and culinary uses. This study concludes that salting is a cost-effective, efficient method for producing high-quality VCO, offering a viable alternative to traditional high-temperature methods.